2005
DOI: 10.1124/mol.104.009340
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Peroxisome Proliferator-Activated Receptor δ Activity Affects Neural Cell Adhesion Molecule and Polysialyltransferase ST8SiaIV Induction by Teratogenic Valproic Acid Analogs in F9 Cell Differentiation

Abstract: It has been suggested that the teratogenic effects of the antiepileptic drug valproic acid (VPA) is reflected in vitro by the differentiation of F9 cells, activation of peroxisome proliferatoractivated receptor ␦ (PPAR␦), and inhibition of histone deacetylases (HDACs). The aim of this study was to identify genes involved in the differentiation of F9 cells induced by VPA, teratogenic VPA derivatives, or the HDAC inhibitor trichostatin A (TSA) and to characterize the role of PPAR␦. Treatment of the cells with te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
(69 reference statements)
2
14
0
3
Order By: Relevance
“…Moreover, the ability of PE-4-yn enantiomers to attenuate the age-related decrease in NCAM polysialylation state suggests that it may have a significant advantage in slowing onset of degenerative deficits by enhancing neuroplasticity. It was found that the expression of PSA-NCAM was increased in a concentration dependent manner by both R-and S-PE-4-yn, an observation consistent with the fact, that the racemic mixture of PE-4-yn enantiomers induces the expression of one of the enzymes, PST1, responsible for attaching PSA to NCAM (Lampen et al 2005). This indicates that R-and S-PE-4-yn have largely similar effects in vitro.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, the ability of PE-4-yn enantiomers to attenuate the age-related decrease in NCAM polysialylation state suggests that it may have a significant advantage in slowing onset of degenerative deficits by enhancing neuroplasticity. It was found that the expression of PSA-NCAM was increased in a concentration dependent manner by both R-and S-PE-4-yn, an observation consistent with the fact, that the racemic mixture of PE-4-yn enantiomers induces the expression of one of the enzymes, PST1, responsible for attaching PSA to NCAM (Lampen et al 2005). This indicates that R-and S-PE-4-yn have largely similar effects in vitro.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, HDAC inhibition is known to enhance NCAM protein expression and the expression of the adult form of polysialyltransferase (PST1) (Lampen et al, 2005). Collectively, these results imply that both the neurobehavioural and neurological deficits induced by in utero exposure to the VPA can be reversed in the adult by use of HDAC inhibitors, such as MS-275.…”
Section: Construct Validity Of Vpa Model Of Asdmentioning
confidence: 95%
“…Par ailleurs, il a été récemment montré que l'acide valproï-que, un activateur de PPARβ/δ, tératogène in vivo chez l'homme et la souris, est capable de moduler l'expression de la molécule NCAM (neural cell adhesion molecule) [2]. PPARβ/δ est normalement exprimé dans les cellules F9 de carcinome embryonnaire et son activation par l'acide valproïque induit la différenciation de ces cellules.…”
unclassified
“…Sa surexpression dans les cellules F9 traitées par l'acide valproïque induit une forte expression du gène codant NCAM, favorisant ainsi l'adhérence et la différenciation des cellules F9. Réciproquement, la répression de l'activité de PPARβ/δ inhibe ces effets [2]. En revanche, l'activation de PPARα ou de PPARγ n'a pas d'effet sur l'expression de NCAM [2].…”
unclassified
See 1 more Smart Citation